Comparative transcriptome and proteome reveal synergistic functions of differentially expressed genes and proteins implicated in an over‐dominant silkworm heterosis of increased silk yield. Issue 5 (19th June 2022) - Xiao, Rui; Yuan, Yi; Xia, Hengchuan; Ge, Qi; Chen, Liang; Zhu, Feifei; Xu, Jia; Wang, Xueqi; Fan, Yixuan; Wang, Qiang; Yang, Yanhua; Chen, Keping
Abstract: We previously observed an over‐dominant silkworm heterosis of increased yield in a cross of Bombyx mori nuclear polyhydrosis virus‐resistant strain NB with a susceptible strain 306. In the present study, we found that heterosis also exists in crosses of NB with other susceptible strains, indicating it is a more general phenomenon. We performed comparative transcriptome and proteome and identified 1624 differentially expressed genes (DEGs) and 298 differentially expressed proteins (DEPs) in silk glands between parents and F1 hybrids, of which 24 DEGs/DEPs showed consistent expression at mRNA and protein levels revealed by Venn joint analysis. Their expressions are completely non‐additive, mainly transgressive and under low‐parent, suggesting recombination of parental genomes may be the major genetic mechanism for the heterosis. GO and KEGG analyses revealed that they may function in generally similar but distinctive aspects of metabolisms and processes with signal transduction and translation being most affected. Notably, they may not only up‐regulate biosynthesis and transport of silk proteins but also down‐regulate other unrelated processes, synergistically and globally remodelling the silk gland to increase yield and cause the heterosis. Our findings contribute insights into the understanding of silkworm heterosis and silk gland development and provide targets for transgenic manipulation to further increase the silk yield. Abstract : The differentially expressed genes (DEGs) and differentially expressed proteins (DEPs) in silk glands are mainly non‐additive, suggesting recombination of parental genomes may be the major genetic mechanism for the heterosis. They may function in signal transduction and translation, up‐regulate biosynthesis and transport of silk proteins.